2017
DOI: 10.1111/nin.12212
|View full text |Cite
|
Sign up to set email alerts
|

The impact of regulatory perspectives and practices on professional innovation in nursing

Abstract: Since at least the 1970s in Canada, there have been calls for health system reforms based on innovative roles and expanded scopes of practice for nurses. Professional regulatory organizations, through legislation, define the standards and parameters of professional nursing practice. Nursing regulators emphasize public protection over the advancement of nursing; regulatory processes and decisions tend to be conservative and risk-averse. This study explored the impact that regulatory processes have on innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…During an assessment of titles and abstracts, 99 articles were excluded due to a lack of relevance. After a full-text review of the remaining 16 articles, only two articles reported on studies specifically related to self-employed nursing regulation: Stahlke Wall (2018) and Hunter et al (2021) .…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…During an assessment of titles and abstracts, 99 articles were excluded due to a lack of relevance. After a full-text review of the remaining 16 articles, only two articles reported on studies specifically related to self-employed nursing regulation: Stahlke Wall (2018) and Hunter et al (2021) .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The study involved eight participants from a single province, which was not disclosed. According to the participants, their interactions with the provincial regulator were highly negative ( Stahlke Wall, 2018 ). The regulator was seen as imposing restrictive, unsupportive, complex, inconsistent, and unclear regulatory processes, which led to feelings of mistrust, powerlessness, and fear ( Stahlke Wall, 2018 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Pri tem je bila kritična do pasivnih sester (K23), ki niso prispevale k razvoju društva in krepitvi moči poklica. Stahlke (2018) opiše nezainteresiranost medicinskih sester kot enega izmed pomembnih dejavnikov razvoja zdravstvene nege kot poklica, medtem ko Gunn in sodelavci (2019) zunanji dejavnik nasprotovanja razvoju vidijo v zdravnikih. S slednjim se je srečevala tudi Angela Boškin med svojim službovanjem v Trbovljah (P76) -podobno kot Florence Nightingale (MacMillan, 2012).…”
Section: Diskusijaunclassified
“…A large body of the literature examined microfactors influencing the development of the nursing profession, including: the inconsistent interest in professionalization among nurses (Kinnear, 1994), the strength of professional associations (Stahlke, 2018), nurses involvement in political advocacy (Adams, 2003), task fragmentation (Coburn, 1994), and medical opposition (Liu, 2011). Numerous other studies investigated factors affecting nursing's development (Canadian Nurses Association, 2013;D'Antonio, Fairman, & Whelan, 2013;Siles, Solano-Ruiz, Fernández de Freitas, & Oguisso, 2010).…”
Section: Current Approaches To the Study Of Nursing Professionalizamentioning
confidence: 99%